Investment in education: Some lessons from the international evidence for the Baltic states - Erich Gundlach (Institut für Weltwirtschaft (IfW), 1999)
The international empirical evidence on the economics of education reveals one central insight and two puzzles, which are all relevant for the case of the Baltic States. The central insight is that social rates of return to education tend to be higher than the social opportunity costs of capital, except for the case of higher education. Based on this microeconomic evidence, the case for public investment in education is well founded, especially at the primary and the secondary levels. The first puzzle is that at the macroeconomic level, the presumed positive link between increases in educational attainment and income growth is difficult to detect. One reason is that a high rate of absorption of well-educated workers by the government sector, typical for many developing countries, is likely to reduce the long-run growth rate. The second puzzle is that there is no clear link between higher spending on educational inputs and higher educational output in the form of improved performance of pupils. As it seems, higher spending on education is not sufficient to improve performance as long as inefficiencies in the schooling system remain. For the Baltic States, three basic lessons emerge from the international evidence: First, public investment in higher education does not show up as a top priority from a social point of view; second, the macroeconomic return to education could turn out to be low if better educated workers predominantly end up in the relatively large government sectors typical for the Baltic States. Third, the productivity of schooling could probably be improved, for instance by a different allocation of resources within the education sector. Most likely, such an outcome would require a fundamental reform of the schooling system itself, not only in the Baltic States.
Keywords: 330; Bildungsinvestition; Studium; Wirtschaftswachstum; Bildungsökonomik; Wirtschaftliche Effizienz; Allokationseffizienz; Öffentlicher Sektor; Welt; Entwicklungsländer; Nordosteuropa